2012
DOI: 10.4038/cjsbs.v41i1.4535
|View full text |Cite
|
Sign up to set email alerts
|

Disease control strategies for extending storage life of papaya (Carica papaya), cultivars 'Red Lady' and 'Rathna'

Abstract: Anthracnose (Colletotrichum gloeosporioides), stem-end rot (Lasiodiplodia theobromae) and Phomopsis rot (Phomopsis caricae-papayae) are major post-harvest diseases in papaya resulting in relatively high postharvest losses, up to 45%, in Sri Lanka. The current consumer preference is for tropical fruits free of synthetic pesticides. The objectives of the present investigation were to identify major post-harvest pathogens in papaya fruits, test in vitro fungitoxic effect of basil oil (Ocimum basillicum) and alum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Papaya cultivars, 'Rathna' and 'Red Lady', stored at 12-14 ˚C following treatment with 1% (w/v) alum (sodium aluminium sulphate) or 1% alum and 0.16% (v/v) basil oil and enclosed in styrofoam sleeves were found free of postharvest diseases including SER (Abeywickrama et al, 2012). No residues of basil oil could be detected on fruit peel by gas chromatography at the end of the experimental period of 14 days (Abeywickrama et al, 2012).…”
Section: Essential Oils With Fungicidal Propertiesmentioning
confidence: 97%
See 2 more Smart Citations
“…Papaya cultivars, 'Rathna' and 'Red Lady', stored at 12-14 ˚C following treatment with 1% (w/v) alum (sodium aluminium sulphate) or 1% alum and 0.16% (v/v) basil oil and enclosed in styrofoam sleeves were found free of postharvest diseases including SER (Abeywickrama et al, 2012). No residues of basil oil could be detected on fruit peel by gas chromatography at the end of the experimental period of 14 days (Abeywickrama et al, 2012).…”
Section: Essential Oils With Fungicidal Propertiesmentioning
confidence: 97%
“…(Hine et al, 1965). Later certain other genera including Botryodiplodia (Hunter and Buddenhagen, 1972;Abeywickrama et al, 2012), Phomopsis and occasionally Fusarium were found in diseased fruits (Hunter and Buddenhagen 1972). A stemend disease of papaya (Carica papaya L.) was reported to be caused by Mycosphaerella sp., the perfect stage of Ascochyta caricae-papayae (Chau et al, 1979).…”
Section: Ser In Avocado Papaya and Rambutanmentioning
confidence: 99%
See 1 more Smart Citation
“…bananas and guava in tropical and subtropical regions in the world (Smoot et al, 1971;Mascarenhas et al, 1995;Alvindia and Natsuaki, 2007;Hashem and Alamri, 2009;Abeywickrama et al, 2012). This postharvest decay can lead to significant economic losses, and the fungus can also cause preharvest diseases on some horticultural crops, such as mango tree dieback disease (Khanzada et al, 2004).…”
mentioning
confidence: 99%
“…Alum at 1% (w/v) prevented mycelial growth of crown rot pathogen L. theobromae and papaya stem end rot pathogen Phomopsis caricaepapayae during in vitro assay (Abeywickrama et al, 2012). Bestoon (2012) epidermidis, E. coli, Klebsiella pneumonia) and the results showed that the 20% of alum was found to be Minimum Inhibitory.…”
Section: Pathological Propertiesmentioning
confidence: 94%